METHOD FOR CALCULATION OF STRESSED STATE SUBSTANTIATED BY DYNAMIC MICROTWIN - V. V. Vlashevich; O. M. Ostrikov (Наука и техника, 2014)
Method for calculation of the stressed state in a dynamic twin has been developed on the basis of a non-thin non-coherent micro-twin model with continuous distribution of twinning dislocations at twin boundaries. In this case there is no additional generation with the help of twinning dislocation source. The model takes into account that the twin has coherent and noncoherent boundary sections. The developed model has made it possible to take into consideration a form of non-coherent sections of twinning boundaries in calculations of stressed and deformed state at dynamic twins. It has been established that localized stresses are migrating together with non-coherent sections of the twin. Normal stresses σxx change their sign in relation to direction of the twin development. Shear stresses σxy are alternating in signs in relation to an axis which is perpendicular to the direction of the twin development and which is passing through a mid-point of non-coherent twin section. Distribution of stresses σyy и σyz has similar configuration. Stresses σzx in the second and fourth quarters of XOY plane are negative and the stresses in the first and third quarters are positive. Distribution of stresses σzz practically does not differ from distribution of stresses σyy according to configuration but numerical values of stress tensor component data are different.The results have been obtained without thin twin model that permits to consider only elastic stage of the twinning process. The executed stress calculations at dynamic twin are important for forecasting at the accumulation stage of damage origination which is caused by twinning destruction and permit to improve forecasting accuracy of technical system resources on the basis of twinning materials such as alloys based on iron, copper, zinc, aluminium, titanium.